Neuropsychiatric Systemic Lupus Erythematosus (NPSLE) – Masquerade Diagnosis: A Case Report - Mohd Hanafi, Mohd Sharil Iman; Che’ Man, Mohammad; Che Alhadi, Shahidah (IIUM Medical Journal Malaysia, 2020)
Introduction: Diagnostic challenge is seen in Systemic Lupus Erythematosus (SLE) due to insidious onset, unpredictable course, broad spectrum of clinical presentation that mimic other diseases manifestation and possibility not fulfilling the classification criteria at the earlier course of the disease. Case report: We highlighted a case of a man, lived with diagnosis of Schizophrenia for almost 15 years subsequently revealed him suffered from neuropsychiatric lupus as he fulfilled the SLE classification criteria. His initial presentation was altered sensorium treated as acute psychosis-the tip of an iceberg to the underlying disease. His multiple admissions to psychiatric ward were believed contributed by episode of lupus flare. Necessary investigation is important to exclude another medical condition before make a diagnosis of Schizophrenia using DSM-V criteria. The misdiagnosis has significantly impaired his social life and untreated disease had leads to morbidity and severe organ damage. This case emphasizes on the crucial aspect of assessing patient as a whole, follow-up the progression and re-evaluates patient’s condition for a new hint. Even though there is no cure yet for SLE, correct and early diagnosis is able to guide for individualized treatment and thus helping in good disease control that warrant better outcome.